2018
DOI: 10.1007/s12026-018-8989-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired natural killer cell subset phenotypes in human obesity

Abstract: Obesity is associated with alterations in functionality of immune cells, like macrophages and natural killer (NK) cells, leading to an increased risk for severe infections and several cancer types. This study aimed to examine immune cell populations and functional NK cell parameters focusing on NK cell subset phenotypes in normal-weight and obese humans. Therefore, peripheral blood mononuclear cells (PBMCs) were isolated from normal-weight and obese individuals and analyzed by flow cytometry. Results show no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 60 publications
4
62
0
5
Order By: Relevance
“…In accordance to the results in mice and rats, obesity was shown to be associated with a decreased NK cell number in blood, liver, uterine, or colon tissue in humans (74,99,(146)(147)(148)(149), whereas several other studies did not observe any differences in the NK cell number comparing normal-weight and obese humans (71,72,84,(150)(151)(152)(153)(154)(155) (Table 4). These discrepancies may be caused by the use of different markers and methods to identify NK cells and subsets in blood and different tissues and individual parameters in the study population, like gender, BMI, ethnicity, and nutritional or metabolic variances.…”
Section: Effects Of Systemic Obesity On Human Nk Cellssupporting
confidence: 84%
See 3 more Smart Citations
“…In accordance to the results in mice and rats, obesity was shown to be associated with a decreased NK cell number in blood, liver, uterine, or colon tissue in humans (74,99,(146)(147)(148)(149), whereas several other studies did not observe any differences in the NK cell number comparing normal-weight and obese humans (71,72,84,(150)(151)(152)(153)(154)(155) (Table 4). These discrepancies may be caused by the use of different markers and methods to identify NK cells and subsets in blood and different tissues and individual parameters in the study population, like gender, BMI, ethnicity, and nutritional or metabolic variances.…”
Section: Effects Of Systemic Obesity On Human Nk Cellssupporting
confidence: 84%
“…Whereas, several studies did not find any differences on the CD56 dim /CD56 bright ratio comparing NK cells isolated from normal-weight and obese humans (72,150,152,156), results of two studies revealed evidence for a decrease of CD56 dim CD16 bright NK cells and an increase of CD56 bright CD16 dim/neg NK cells in obesity (71,147). As previous studies observed that the CD56 dim CD16 bright NK cell subset can convert into the CD56 bright CD16 dim subset under the influence of specific cytokines and hormones, it had been assumed that obesity-related metabolites induce a conversion of CD56 dim CD16 bright in CD56 bright CD16 dim/neg NK cells in obese individuals (71,(162)(163)(164). Analyses of the subset-specific NK cell phenotype also demonstrated a decrease in NKG2Dpositive and CD69-positive CD56 dim CD16 bright NK cells (71).…”
Section: Effects Of Systemic Obesity On Human Nk Cellsmentioning
confidence: 80%
See 2 more Smart Citations
“…Impairing of the NK cell function is one of the common factors behind these links. For example, obesity has been known to impair NK cell function and then lead to an increased risk for severe infections and several cancer types ( 48, 49 ), while chronic family stress is consistently associated with decreases in NK cell cytotoxicity ( 50 ). These results indicated that NK function impaired by either genetic defects or regulatory factors such as depression, obesity and diabetes could increase cancer incidence.…”
Section: Resultsmentioning
confidence: 99%